(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The article discusses the strategic role of data management frameworks in modern business and financial sectors. Efficient collection, storage, and processing of data not only enhance real-time decision-making capabilities but also play a critical role in strategic planning and risk assessment. By integrating data from diverse sources and leveraging analytical tools, these frameworks enable organizations to respond swiftly to market changes and secure competitive advantages. Managing both structured and unstructured data effectively, data management frameworks harness the potential of modern information technologies to improve decision support systems. The research emphasizes the overall significance of these frameworks and highlights the necessity for their continual enhancement in the future. Key words: data management framework, data management strategies, data governance, data governance roles, data quality, data glossary, data lineage.